IMPACT OF CLASS ATTENDANCE UPON EXAMINATION RESULTS OF STUDENTS IN BASIC MEDICAL SCIENCES - Khan, Habib -ullah; Khattak, Aziz Marjan; Mahsud, Ihsan -ullah; Munir, Akhtar; Ali, Shaukat; Khan, Muhammad Hussain; Saleem, Muhammad; Shah, S. Hamayun (Journal of Ayub Medical College Abbottabad, 2003)
Background: A number of studies have shown the impact of attending the classes during the session on examination results of students. Students with good lecture attendance show good results while those with poor lecture attendance are at risk for poor performance in the examinations. In this study we wanted to test this in students of basic medical sciences in our set up. Methods: All the students in Basic Medical Sciences of Gomal Medical College, D.I. Khan, Pakistan, during the session 1999-2000 were enrolled for this study. Performance of these students in one of their three annual term tests, which covered duration of studies for four months, from February 2000 to May 2000, was analyzed. Students were grouped into two, Group-A with ‰¥75% attendance and Group-B with <75% attendance. The frequency of failure in the two groups was compared using the chi square test. Results: Results of the term test showed that the percentage of failure in students of Group-B with less than 75%, attendance was significantly higher when compared to Group-A with equal or more than 75 % attendance. Conclusion: Our results supported the previous studies showing that attendance in the classes during teaching sessions had a direct impact on performance of students in the examinations. Students with good attendance show good results while those with poor attendance are at risk for poor performance during examinations in basic medical sciences. Keywords: Student, Attendance, Examination, and Performance.